Exploring Deadweight Loss of Potential Regional Revenue Lost Due To Prostitution Practices in Palangka Raya - Muhammad Farras Nasrida; Suherman Suherman; Dicky Perwira Ompusunggu; Tiur Roida Simbolon (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The underground economy, often referred to as the informal economy, encompasses various economic activities that are unrecorded in formal economic systems and not reported to the government. These activities frequently operate outside legal frameworks or exist within regulatory gray areas, including drug trafficking, tax evasion, and prostitution. The underground economy continues to grow, particularly in rapidly expanding cities. In Palangka Raya, the capital of Central Kalimantan Province, this phenomenon has become significant, with prostitution standing out as a prominent sector. This study investigates the potential revenue lost due to prostitution activities in Palangka Raya, where practices, both offline and online, generate income for those involved but remain untaxed. Despite efforts to reduce such activities, prostitution persists in some areas, both in former red-light locations and covertly through digital platforms. This situation poses not only social and security risks for the community but also results in lost potential revenue that could otherwise support local development initiatives.